Les transformations d’un faubourg de Blois : les terrasses de l’Évêché (ve-xixe siècle) - Marie-Denise Dalayeun; Jérôme Bouillon; Françoise Yvernault (Revue Archéologique du Centre de la France)
The excavation carried out in 2011 at the “Terrasses de l’Évêché” behind the Saint-Louis Cathedral in Blois (Loir-et-Cher) brought to light remains dating from the 5th to the 19th century. The discovery of a dense funerary area, whose first burials date back to around the 5th-7th c., reveals that an important cemetery was linked to the Saint-Solenne church, future Saint-Louis cathedral. Furthermore, domestic remains from the 11th-13th c. (silos and post holes) were first in the vicinity of the cemetery before gradually shifting westwards, probably in relation with the cemetery’s retraction towards the church and the progressive abandonment of the burial area.The survey of part of the urban enclosure ditch confirms its digging before the 14th century while regularly maintained by successive cleanings during the 14th and 15th centuries. At the end of the 16th century, the ditch was largely backfilled and no longer fulfilled its defensive role.The development of the terraces by the addition of a large embankment took place as early as the 15th century, as evidenced by the remains of a building built partly over the ditch. This area was part of the Faubourg Saint-Jean, which, according to written sources, was settled at the end of the 14th century.Finally, two masonry latrines are linked to the development of the terraces and gardens in relation with the creation of the episcopal palace in the mid-18th century.